A crítica social em João Ternura, de Aníbal Machado: identidade nacional, modernidade e o carnaval como momento de compensação - Mendes, Taísa Pereira Ferreira (2015)
This research aims to analyze both the writer s role in the social context of Brazil of the twentieth century first half as the criticism to the modern Brazilian society in the novel John Tenderness, by Aníbal Machado, denouncing its problems. Qualitative, this work combines the readings of theoretical foundation, emphasizing the names of Roberto DaMatta, Sérgio Buarque de Holanda, Roberto Schwarz, Edward M. Forster, Tveztan Todorov, Roland Barthes and Sérgio Miceli, with the interpretation of the literary object. Firstly, it examines the writer s new active and questioning positioning towards social reality, after the modernist movement. Among this group, it emphasizes the committed action of Aníbal Machado, especially during the First Brazilian Congress of Writers. Sequentially, it analyzes the structural aspects of the novel, as the plot and the space, focusing for the investigation of some national stereotypes represented in the characters of the work. After this structural survey of the work which allowed greater breadth of its meaning, an analysis is made of some common identity features among Brazilians in general, determining the contradictions occurred in the country due to poor planning for the entry into the modernity and the arrival of modernization exposed in the book. With that, having an exclusive national reality, oppressive and stuck to hierarchies, it is clear that Carnival, narrated in chapter six of the novel, holds the compensation function of this everyday world. That s because all the different classes, races and cultures become equal to celebrate the occasion in which everything is permitted. In the end, John Tenderness realizes that the carnival party is just an appointment for joy, everyone returns to the routine where the social position of each one is clearly defined.